Saturday

April 19, 2014

April 19, 2014

Posted by **Lori** on Monday, March 29, 2010 at 8:13pm.

5(n+3)=2(2n+6)

Simplify

4(x-1)+2(x+4)

- MATH -
**Kathleen**, Monday, March 29, 2010 at 8:24pm5n+15=4n+12

-4n -4n

n+15=12

-15 -15

n=-3

Check 5(-3+3)=3(2*-3 +6)

5(0)=3(16+6)

0=3(0)

0=0

4x-4+2x+8

6x+4

- MATH -
**Lori**, Monday, March 29, 2010 at 9:37pmThank you

**Related Questions**

MATH - Solve the equation 5(n+3)=2(2n+6) Simplify 4(x-1)+2(x+4)

algebra - So... I know the answer to the question because it's something we ...

algebra - Find two consecutive positive integers such that the sum of their ...

Math - How would I begin to simplify this?? (4((n(n+1)(2n+1))/6)-4((n(n+1))/2)+n...

maths - 2(n-5) = 4 (n+2) Solve the equation is the answer -0.3 ? 2(n-5) = 4 (n+2...

bobpursley, math,correction - Let n be a postive integer, then n+1 is the next ...

math - Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T ...

8th grade math Ms. Sue - How is an inequality different from an equation? Give a...

math - question 1 use the laws of logarithms to simplify the expression Inx(x+2...

Math - Pre-Calc - So far I got it down to ((4/3)n^3+(11/6)n^2)/((4/3)n^3)+(2n^2...